Acessos e barreiras à cidadania: as Organizações Sociais e as novas formas de gestão do espaço público nas cidades paraenses - BAENA, Silvia Cristina Pereira (Universidade Federal do Pará, 2022)
The growth of the urban population is still a recurring problem that has serious impacts on cities, revealing a sharp contrast through socio-spatial and environmental transformations, which generates a process of territorial segregation. After all, urban growth does not necessarily come with better conditions of access to urban land. In addition, changes in the socioeconomic scope have redirected the management of cities and imposed models and parameters so that metropolises are readapted in order to make them more attractive. This scenario has also been repositioning the role of the State in the production of the city, especially with regard to new forms of management, which involves incentives beyond conventional public management. In this sense, this work aims to analyze the advances and limits of the management and planning model implemented by the public-private partnership between the Government of the State of Pará and the Pará 2000 Social Organization, in public spaces in Belém (Hangar, Mangal das Garças, Estação das Docas and Mangueirinho), from the point of view of citizenship and universal access to the service offered. This thesis starts from the criticism of political administration, which intends to think about public management from a critical perspective in accordance with the method of interpretation of historical-dialectical materialism, of a qualitative-explanatory nature. For data analysis, a triangulation strategy was adopted (interviews, documents and systematic observation), while, for categorization, a logical matrix on the topics raised, using the technique of content analysis. From the data collected, systematized and analyzed, it was found that the State, when using the management model implemented by the public-private partnership in the latter, as a result of neoliberal policies of its management reform project, strategically uses such partnerships in the with the aim of promoting the strengthening of the market, based on a corporate government, moving away from a conception of social justice with a socio-spatial development perspective, which allows universal access for the population. On the contrary, these partnerships, by providing, through contracts, the right to exploit services in exchange for financing and maintenance of the structure, made it possible to understand that the subversion of the criteria for providing the public service, from the importation of economic logics mercantile, with the prerogative that the private sector exercise more effectively the provision of services, depoliticized the relations between the State and citizens. So much so that, with this new reality, in which the company’s congruence, advocated by society’s policy, is universalized, the citizen is now seen as a consumer. In this way, priority is given to the dimension of efficiency and financial return. Therefore, new elements are observed, which make it possible to understand how the strategies, peculiar to the process of diffusion of the capitalist mode of production and free competition, advance in society from this new neoliberalist reason, which has transformed capitalism by establishing a set of policies, rules, norms of conduct and practices, as well as social control mechanisms that expand its influence in the world. This reality has guided nations and their governments, companies and subjects that regulate their actions from a subjectivity structured in the entrepreneurial logic.